Superiority Of Fatherhood Reflected In Terrence Malick's The Tree Of Life Movie (2011): An Individual Psychological Approach - Yunita, Astuti Lisa Nurma, Dr. Phil. Dewi Candraningrum, S.Pd, M. Ed, Drs. H. Abdillah Nugroho, M. Hum (2013)
The major problem of this study is how meaning of superiority of fatherhood is reflected in Terrence Malick's The Tree of Life movie (2011). The study is aimed to analyze the movie based on structural elements and to analyze the movie based on the individual psychological approach. The object of this study is The Tree of Life movie by Terrence Malick. This study belongs to descriptive qualitative research. There are two types of data source. First, the primary data is The Tree of Life movie that was released in 2011 and the secondary data are books or any information relation to the practice of superiority of fatherhood that support an individual psychological approach. Both data are collected through library research and analyzed by descriptive analysis. Based on the analysis, the researcher draws the following conclusions. First, based on the structural analysis of each element, it shows that the character and characterization, casting plot, setting, point of view, theme, mise-en-scene, cinematography, sound, and editing are related to each other. Second, based on the individual psychological analysis, the notion of superiority, basic concept of fatherhood, father's influence on children is reflected in Mr. O'Brien's life. All of them involved in the process of Mr. O'Brien becoming fatherhood.